Heparin-induced bleeding treatment in microsurgery - Mendoza-Aceves, Rodrigo A.; Banegas-Ruiz, Rodrigo; Gómez-Mendoza, Francisco Fabián; Román-Hernández, Rigoberto; Porras-Méndez, Christian; Valderrama-Treviño, Alan I.; Vejar-Alba, Ismael; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2019)
Microsurgery is associated with prolonged surgical times with an increased risk of deep vein thrombosis, pulmonary embolism and myocardial infarction. The use of antithrombotic means is a commonly employed tactic to prevent vascular thrombosis after microvascular free flap surgery. Flap loss is a devastating complication of microsurgical procedures that leads to detrimental outcomes. A 32-year-old male patient has a ruptured calcaneal tendon. He underwent 5 surgical cleanings with multiple failed sequential attempts at wound closure. Traumatology department in its microsurgery division where it is proposed to perform neo-tendon with graft of palmaris longus of the right thoracic extemity and radial antebrachial microvascular flap. The neo tendon was performed in addition to the micro surgical coverage with the radial antebrachial flap.When having vascular control with micro-clamps, 6000 U of unfractionated heparin was initiated, approximately 20 minutes after the end of the microvascular anastomosis, there was incoercible bleeding, which is initially treated with spray fibrin. Continued bleeding after 3 hours, so it was decided to reverse the effect of heparin with transfusion of fresh frozen plasma, 10 mg of vitamin K and fibrinogen. The effect of heparin was reversed without having thrombotic complications of microvascular anastomoses. The flap was not reexplored since they showed no signs of vascular compromise. If anticoagulants have been used and an incoercible hemorrhage is found, the effect of heparin must be reversed. In the transfer of tissues with microsurgery, the recommended and safe anticoagulation are prophylactic doses and not therapeutic doses.